Analisis Pemanfaatan Barang Gadai dalam Perspektif Fiqh Madzhab Syafi’i dan Ketentuan Fatwa DSN-MUI No.25/DSN-MUI/III/2002 - Hamid, Abdul; Komarudin, Udin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to explore in depth the legal provisions regarding the utilisation of collateral (marhun) in a pawn contract (rahn) based on the perspective of the Shafi'i Madzhab and the contemporary provisions contained in the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) No. 25/DSN-MUI/III/2002. The study was conducted using a normative juridical approach and comparative analysis of classical fiqh literature and contemporary regulations. The results show that the Shafi'i Madzhab affirms the absolute prohibition of taking the benefits of collateral except for maintenance purposes, in order to avoid elements of usury and injustice. Meanwhile, the Fatwa of DSN-MUI allows the collection of benefits in certain situations provided that the agreement is transparent and the calculation of benefits is proportional. This research reveals how the interpretation of Islamic law can be dynamic in responding to modern economic challenges, while still maintaining the basic principles of sharia. The results of the study are expected to strengthen the normative basis of Islamic pawn and become a reference for policy harmonisation between classical fiqh and Islamic banking practices.